Visual assessment of colour rendering. Volume One - Corrigall, Michael Robert Vint (Department of Electrical Engineering, 2024)
The first part describes experimental work done which led to the construction of a portable pocket filter instrument which made it possible to assess the C.I.E. Colour Rendering Index for fluorescent lamps by a simple visual testo Research !uork was done on filter devices in the laboratory, and the results processed by digital computer. The second part deals with a visual problem. Tests done using filter devices indicated two groups of observers with normal colour vision. After an experimental investigation on a few observers, this problem was overcome by using a pale yellow filter in the instrumentc Details of the computer programme and experimental details are described in appendices. Records are contained in a separate volume